A new interpretation of the defense glands of neotropical Ruptitermes (Isoptera, Termitidae, Apicotermitinae) - Costa-Leonardo, A. M. [UNESP] (My University, 2004)
Suicidal altruism has been reported for some species of eusocial insects, in which the individual dies in defense of the society. The termites of the genus Ruptitermes are known for the suicidal behavior of the workers which liberate a sticky defensive secretion by body bursting. In the present paper it is given a new interpretation of the defense glands of Neotropical Ruptitermes based on the morphological analysis of three species collected at Rio Claro, SP, Brazil. Before the current study, the suicidal defensive behavior was attributed to the dehiscence of the salivary gland reservoirs. The defense or dehiscent glands of Neotropical Ruptitermes are pair structures rounded in shape that are independent of the salivary glands. The dehiscent glands consist of multiple secretory units that are kept together by thin connective tissue. Each secretory unit is composed of one cell generally with one peripheral nucleus and characteristic secretion. The three species studied here present some histological differences in the secretory units, probably related to the chemical composition of the secretion.
Keywords: Autothysis; Defensive behavior; Dehiscent glands; Salivary glands; Termites; Apicotermitinae; Hexapoda; Insecta; Isoptera; Termitidae